On the Impact of Tsallis Statistics on Cosmic Ray Showers - M. Abrahão; W. G. Dantas; R. M. de Almeida; D. R. Gratieri; T. J. P. Penna (Advances in High Energy Physics)
We investigate the impact of the Tsallis nonextensive statistics introduced by intrinsic temperature fluctuations in p-Air ultrahigh energy interactions on observables of cosmic ray showers, such as the slant depth of the maximum Xmax and the muon number on the ground Nμ. The results show that these observables are significantly affected by temperature fluctuations and agree qualitatively with the predictions of Heitler model.